An Exposition of AVM Performance Metrics. Issue 1 (1st January 2020) - Ecker, Mark; Isakson, Hans; Kennedy, Lee
Abstract: This case presents a thorough exposition of the state of the art in the calculation and interpretation of automated valuation model (AVM) performance metrics, including the forecast standard deviation (FSD), confidence scores, vertical and horizontal equity, and error buckets. It also discusses the failure rate, failure magnitude, and failure median absolute percentage error (MAPE) metrics, which focus on tails of an AVM's distribution of errors. In addition, this case demonstrates the calculations and relationships between the AVM performance metrics using a regression model and property sales from a medium-sized Midwestern college city.